2014
DOI: 10.1179/1743676114y.0000000212
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal OsB2reduction upon heating in H2containing environment

Abstract: The stability of hexagonal ReB 2 type OsB 2 powder upon heating under reforming gas was investigated. Pure Os metal particles were detected by powder X-ray diffraction starting at 375uC and complete transformation of OsB 2 to metallic Os was observed at 725uC. The mechanisms of precipitation of metallic Os is proposed and changes in the lattice parameters of OsB 2 upon heating are analysed in terms of the presence of oxygen or water vapour in the heating chamber. Previous studies suggested that Os atoms posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It was generally concluded that the presence of elemental boron and a sufficient concentration of highly volatile reactants at the reaction front were prerequisites for a successful compound formation [6], as attempts to synthesise AlMgB 14 using AlB 12 and MgB 2 compounds as reactants resulted in only 25 vol.-% yield of AlMgB 14 phase in the product mix of other phases [39]. Oxidation is a common problem during synthesis of boride compounds [44][45][46][47]. The formation of MgAl 2 O 4 spinel was always reported in all synthesis attempts as a result of contamination of reactants and inevitable presence of oxygen that facilitated and was responsible for formation of thermodynamically stable oxide.…”
Section: Introductionmentioning
confidence: 99%
“…It was generally concluded that the presence of elemental boron and a sufficient concentration of highly volatile reactants at the reaction front were prerequisites for a successful compound formation [6], as attempts to synthesise AlMgB 14 using AlB 12 and MgB 2 compounds as reactants resulted in only 25 vol.-% yield of AlMgB 14 phase in the product mix of other phases [39]. Oxidation is a common problem during synthesis of boride compounds [44][45][46][47]. The formation of MgAl 2 O 4 spinel was always reported in all synthesis attempts as a result of contamination of reactants and inevitable presence of oxygen that facilitated and was responsible for formation of thermodynamically stable oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mechanochemical syntheses have been employed in the preparation of such difficult to process boron-rich solids as ReB 2 and OsB 2 ceramics. [30][31][32][33] Mechanochemical synthesis usually involves the high energy milling of powder using special mills where the milling occurs by high axial and shear forces produced by frequent impact events when balls hit the walls of the milling vial. A movie illustrating the ball movement and applied impact axial and shear stresses during high-energy ball milling can be found in the online supporting information.…”
Section: Introductionmentioning
confidence: 99%
“…This significantly limited their useful applications. Recent work on the synthesis and properties of ReB 2 , OsB 2 , and IrB 2 compounds have shown them to have remarkable mechanical properties, such as high hardness and stiffness, but the stability of these compounds upon exposure to oxygen‐containing species remained uncertain . It was reported that interaction of ReB 2 with water present in air, at RT, led to the formation of perrhenic acid [Re 2 O 7 (OH 2 ) 2 ] followed by a complete degradation of the mechanical properties of the material .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the synthesis and properties of ReB 2 , OsB 2 , and IrB 2 compounds have shown them to have remarkable mechanical properties, such as high hardness and stiffness, [14][15][16][17][18][19][20][21] but the stability of these compounds upon exposure to oxygen-containing species remained uncertain. [22][23][24] It was reported that interaction of ReB 2 with water present in air, at RT, led to the formation of perrhenic acid [Re 2 O 7 (OH 2 ) 2 ] followed by a complete degradation of the mechanical properties of the material. 25 The presence of small amounts of oxygen, when heating hexagonal OsB 2 (h-OsB 2 ) powders, resulted in the formation of boron vacancies, negative thermal expansion, formation of boron oxides, and even the precipitation of metallic Os.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation